Morbillivirus de los Delfines: Patógeno re-emergente en la población de cetáceos - Echeverri-Zuluaga, Manuela; Grupo de Investigación CENTAURO, Facultad de Ciencias Agrarias, Universidad de Antioquia, Calle 70 No. 52-21, Medellín, Colombia (2014)
Dolphin morbillivirus (DMV) is one of the most important pathogen of cetaceans. It was first described in the late 80s, since has been causing outbreaks that affects dolphin populations and also in other cetaceans in the U.S. and in the Mediterranean sea. We conducted a bibliographic search in MedLine, SciELO, Scopus® and Google Scholar without timeline limits using MeSH terms such as Cetacean morbillivirus, Pilot Whale morbillivirus, Dolphin morbillivirus, Strandings, etc., with the aim of provide a critical update on basic, clinical and epidemiological aspects of one of the most important emerging infections for cetacean wildlife, with particular emphasis on the current alternatives for diagnosis and control. Based on the information gathered we concluded that there is not only a need to study and quantify the strandings, but we need to develop awareness of the importance of this viral infection in cetaceans and to apply effective management plans that maintain those populations in biological balance.